Implementasi Smart Attendance System Berbasis RFID dan Face Recognition untuk Meningkatkan Efisiensi Presensi Siswa Pada SMK PAB 8 Sampali Medan - Ommi Alfina; Nita Syahputri; Habib Nurlutman Hasibuan; M. Safii; Muhammad Taufiq Rustam (Universitas Methodist Indonesia, 2026)
The development of digital transformation in the field of education encourages schools to adopt technology that can improve the effectiveness of academic administration, particularly in the student attendance system. SMK PAB 8 Sampali Medan still faces several problems in the conventional attendance process such as delays in recording, potential manipulation of attendance, and suboptimal monitoring of student attendance data. This community service activity aims to implement a Smart Attendance System based on RFID and Face Recognition to improve the efficiency, accuracy, and security of the student attendance process. The implementation of the activity is carried out through stages of observing the school's needs, system design, installation of RFID devices and face recognition cameras, training teachers and school operators in using the system, and assistance in implementation. The results of the activity show that the implemented system is capable of accelerating the student attendance process in real-time, minimizing recording errors, improving student attendance discipline, and facilitating the school in monitoring and digitally summarizing attendance data. In addition, this activity also improves technology literacy for teachers and administrative staff in supporting the digital transformation of education within the school environment.